Political Economy Analysis in Sudan: Handy Tools for Everyone? - Jones, Beverley; Oosthuizen, Daniel (TWP CoP, 2024)
Based on a case study of the Kullana Liltanmia (All of Us for Developm ent) (KLP) Contextual Analysis (CA) course in Sudan, this paper tells the story of how training and capacity building in Political Economy A nalysis (PEA) made a difference in the lives and experiences of those involved, including in particular young people. The paper highlights t hree critical lessons: • At the country level, the twists and turns of Sudan’s recent history reinforce the importance of people deepening t heir understanding of what is really going on, in order to make better informed (if not the best or least-worst) choices. The skills and min dset of both broad and localised PEA capacity can make a difference to people living in fragile and conflict-affected settings, where naviga ting complexity and uncertainty is a daily reality. • At the level of strategic programming, the potential of PEA remains under-utilised. Th ere is considerable scope for capacity in PEA to support not only ordi nary people across a range of different occupations and educational le vels, but also prominent actors who may eventually play key roles in p olitical processes, and whose choices can affect the longer-term prosp ects for stability and peace. This becomes even more imperative in the context of the war in Sudan, which now involves a plethora of externa l actors. • At the level of the experiment in the KLP CA course, this story reinforces the paramount importance of adapting and grounding PE A training in a common understanding among its intended participants, shaping it through their insights and experience. It also highlights h ow essential it is to nurture PEA skills and mindsets not only in stab le contexts but also in challenging, more dangerous and uncertain ones . Supporting this vital capability during periods of hiatus, fast-movi ng transitions, and even active conflict is a public good; and it requ ires courage and creativity on the part of the donors, course designer s, implementers and participants. The paper is structured as follows. Section 1 provides an introduction setting out the broad context of Su dan within which the KLP CA training took place. Section 2 describes t he 30-year period of al-Bashir’s regime (1989-2019). Section 3 focuses on successive UK governance programmes in Sudan between 2015 and 2019 . Section 4 describes the KLP CA course (2017-2018) and its developmen t. Section 5 looks at the revolutionary hiatus and brief transition to civilian rule in Sudan (2017-2018). This is followed by an account in Section 6 of the 2019-2023 transitional phase and dashed hopes for a move to civilian rule with the outbreak of a civil war that has led to exceptional violence (including weaponised sexual violence), displace ment and hunger. Section 7 concludes with reflections on missed opport unities to capitalise on the KLP CA experiment, and with recommendatio ns on the need for continued support on PEA for Sudanese people and or ganisations.